Multilayer electrode and preparation method thereof

By adopting a multi-layer electrode structure in lithium-ion batteries, using the viscosity difference design of conductive agents and active material layers, the porosity gradient of the electrode is optimized, and the problem of contradictory energy density and charging speed of lithium-ion batteries is solved, and the circulation of the battery is improved Performance and rate performance.

CN119252847APending Publication Date: 2025-01-03SHANGHAI AOWEI TECH DEV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411267298.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

There is a contradiction between the energy density and charging speed of lithium-ion batteries, and it is difficult for the prior art to improve their magnification and cycling performance at the same time.

Method used

Using a multi-layer electrode structure, the current collector layer, the conductive layer, the first active material layer and the second active material layer are sequentially from bottom to top. The conductive agent is composed of carbon black, carbon nanotubes, etc., the first active material layer and the first active material layer and the first The viscosity difference design of the two active material layer is prepared by wet coating or dry multilayer coating method to optimize the porosity gradient of the electrode.

Benefits of technology

It improves the cycling performance and charge storage ability of the electrode, improves the electrolyte infiltration and charge and discharge performance, improves the conductivity of the electrode sheet, reduces the polarization of the battery charge and discharge process, and enhances the battery rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005037511590000161
    Figure BDA0005037511590000161
  • Figure BDA0005037511590000171
    Figure BDA0005037511590000171
  • Figure HDA0005037511600000011
    Figure HDA0005037511600000011
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to the field of IPC H01M4, and more particularly relates to a multilayer electrode and a preparation method thereof. The solar cell sequentially comprises a current collector layer (1), a conductive layer (2), a first active material layer (3) and a second active material layer (4) from bottom to top. The two active material layers are arranged, different component formulas are designed, and the thickness ratio of the first active material layer to the second active material layer is (1-2): (1-4), so that the cycle performance of the electrode can be improved; the current collector layer is a copper foil subjected to corrosion treatment, and the corrosion condition is that the copper foil is corroded for 2-5 hours by using a 2.5 wt% acid solution, so that the contact area and the mechanical anchoring force between the foil and other materials can be increased, and the bonding strength between multiple layers of electrodes can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors and batteries, in particular to the field of IPC H01M4, and more specifically to a multilayer electrode and a preparation method thereof. Background Art

[0002] As a new type of energy storage device, lithium-ion batteries are widely used in electronic products, electric vehicles, power grids and other fields. The performance indicators of lithium-ion batteries, such as energy density and charging rate, are increasingly valued by product developers. However, generally speaking, there is a certain contradiction between energy density and charging speed, that is, the higher the energy density, the lower the charging speed, and the higher the charging speed, the lower the energy density. Therefore, how to improve the performance of lithium-ion batteries, such as rate and cycle, has become a technical breakthrough.

[0003] CN111916757B discloses a multilayer electrode and a lithium-ion battery, wherein the multilayer electrode comprises a current collector, a first conductive layer and a second conductive layer, wherein the first conductive layer and the second conductive layer are sequentially stacked on the surface of the current collector, the surface density of the first conductive layer is less than the surface density of the second conductive layer, the thickness of the first conductive layer is less than the thickness of the second conductive layer, and the second conductive layer is partially embedded in the first conductive layer, thereby reducing the expansion effect of the conductive layer of the battery pole piece. This invention involves a multilayer conductive layer, but does not involve a multilayer active material layer. Summary of the invention

[0004] A first aspect of the present invention provides a multilayer electrode, which comprises, from bottom to top, a current collector layer, a conductive layer, a first active material layer and a second active material layer.

[0005] The conductive paste of the conductive layer comprises raw materials for preparing the conductive paste, which include a conductive agent and a binder, wherein the mass ratio of the conductive agent to the binder is (5-20): (0.4-4).

[0006] Preferably, the mass ratio of the conductive agent to the binder is (5-20):(0.4-4).

[0007] The conductive agent includes at least one of carbon black, activated carbon, carbon nanotubes, nitrogen-doped carbon nanotubes, graphene, graphene oxide, nitrogen-doped graphene, and nitrogen-doped graphene oxide.

[0008] Preferably, the conductive agent includes at least one of carbon black and carbon nanotubes.

[0009] More preferably, the aspect ratio of the carbon nanotubes is greater than 500.

[0010] The binder includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polyacrylonitrile, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polysiloxane, polyimide, acrylonitrile multipolymer, polyacrylic acid, and styrene-butadiene rubber.

[0011] Preferably, the binder includes at least one of polyvinylidene fluoride, acrylonitrile multipolymer, polyacrylic acid, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and styrene-butadiene rubber.

[0012] The viscosity of the first active material in the first active material layer at 25° C. is 1800 to 12000 mPa·s.

[0013] The viscosity of the second active material in the second active material layer at 25° C. is lower than the viscosity of the first active material, and the difference between the two viscosities is not less than 1000 mPa·s.

[0014] The first active material layer accounts for more than 80 wt % of the first active material, and the second active material layer accounts for more than 80 wt % of the second active material.

[0015] Preferably, the raw materials for preparing the first active material include: a first active material, a binder, a conductive agent, and a solvent.

[0016] Preferably, the weight ratio of the first active material, the binder and the conductive agent is (80-96):(2-6):(1-3).

[0017] Preferably, the solvent comprises water or N-methylpyrrolidone.

[0018] Preferably, the raw materials for preparing the second active material include: a second active material, a binder, a conductive agent, and a solvent.

[0019] Preferably, the weight ratio of the second active material, the binder and the conductive agent is (80-96):(2-6):(1-3).

[0020] Preferably, the solvent comprises water or N-methylpyrrolidone.

[0021] Preferably, the first active material in the first active material layer accounts for more than 85 wt %, and the second active material in the second active material layer accounts for more than 85 wt %.

[0022] The first active material includes at least one of a negative electrode active material or a positive electrode active material; the negative electrode active material includes: primary particle graphite, secondary particle graphite, silicon carbon, and hard carbon; the positive electrode active material includes: activated carbon, single crystal ternary material, polycrystalline ternary material, lithium manganese oxide material, lithium iron phosphate material, layered oxides that can be used for sodium ion batteries, Prussian blue compounds, Prussian white compounds, and polyanionic compounds.

[0023] The second active material includes at least one of a negative electrode active material or a positive electrode active material; the negative electrode active material includes: primary particle graphite, secondary particle graphite, silicon carbon, and hard carbon; the positive electrode active material includes: activated carbon, single crystal ternary material, polycrystalline ternary material, lithium manganese oxide material, lithium iron phosphate material, layered oxides that can be used for sodium ion batteries, Prussian blue compounds, Prussian white compounds, and polyanionic compounds.

[0024] The D50 particle size of the primary graphite particles is 10-30 microns, and the D50 particle size of the secondary graphite particles is 5-15 microns.

[0025] A second aspect of the present invention provides a method for preparing a multilayer electrode, comprising one of the following methods: wet coating, dry multilayer lamination.

[0026] The wet coating process comprises the following steps:

[0027] S1, coating the conductive slurry on the current collector layer, and after drying, preparing a current collector layer coated with a conductive layer;

[0028] S2, applying the first active material and the second active material on the conductive layer, and drying, to obtain the first active material layer and the second active material layer on the conductive layer.

[0029] The dry multi-layer lamination comprises the following steps: firstly making a single-layer dry electrode sheet, then laminating a plurality of single-layer dry electrode sheets in a multi-layer manner, and finally laminating the laminated electrode sheet with a current collector layer.

[0030] Preferably, the dry multilayer lamination includes the following steps: applying a conductive slurry on a current collector layer, and after drying, preparing a current collector layer coated with a conductive layer; making a single-layer dry electrode sheet of a first active material layer and a second active material layer; and laminating the first active material layer and the second active material layer to the current collector coated with a conductive slurry by thermal lamination.

[0031] The conductive layer can be coated in advance and ready for use.

[0032] Preferably, the current collector layer is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with a 2.5 wt % acid solution for 2 h to 5 h.

[0033] The thickness ratio of the first active material layer to the second active material layer is (1-2):(1-4).

[0034] The applicant has found that the stable cycle of the corresponding lithium-sulfur battery is achieved through the gradient change of the porosity of the multi-layer electrode structure. It may be that the stable cycle of the corresponding lithium-sulfur battery is achieved through the gradient change of the porosity of the multi-layer electrode structure.

[0035] The thickness of the first active material layer is 120-350 microns.

[0036] The coating method in step S1 can be achieved by transfer coating, extrusion coating and other coating methods, preferably slit extrusion coating.

[0037] The step S2 can be implemented by coating multiple layers simultaneously or by coating multiple times.

[0038] When the method is implemented in multiple layers, after the coating of the bottom layer of active material coating is completed, the temperature needs to be lower than the boiling point of the active material slurry solvent in this layer.

[0039] The distribution design of the electrode active material layer can be adjusted according to the actual electrode design performance target, and the electrode active material of each layer can adopt different active material main materials, formulas and slurry solid content.

[0040] Beneficial effects:

[0041] 1. The present application sets up two active material layers and designs different component formulas, and the thickness ratio of the first active material layer and the second active material layer is (1-2): (1-4), which can improve the electrode cycle performance.

[0042] 2. The current collector layer is a copper foil after corrosion treatment, and the corrosion conditions are: 2.5wt% acid solution corrosion for 2h to 5h, which can help increase the contact area and mechanical anchoring force between the foil and other materials, and improve the bonding strength between the multilayer electrodes.

[0043] 3. The multilayer electrode preparation method of the present application is simple and can be designed and adjusted according to the actual electrode design performance objectives.

[0044] 4. The viscosity of the second active material in the second active material layer at 25° C. is higher than that of the first active material, and the difference in viscosity between the two is not less than 1000 mPa·s, which can improve the charge storage capacity of the electrode per unit volume.

[0045] 5. The multilayer composite electrode prepared in the present application can better infiltrate the electrolyte, improve the charge and discharge performance, increase the conductivity of the electrode, reduce the polarization of the battery during charge and discharge, and improve the battery rate performance.

[0046] 6. The multilayer composite electrode prepared in this application is used for the preparation of electrodes for supercapacitors, lithium-ion batteries, sodium-ion batteries, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Schematic diagram of a multilayer electrode, wherein 1 is a current collector layer; 2 is a conductive layer; 3 is a first active material layer; and 4 is a second active material layer. DETAILED DESCRIPTION

[0048] Example 1

[0049] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0050] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0051] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0052] The raw materials for preparing the conductive paste are: a conductive agent (carbon black, Super-p), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:99.

[0053] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0054] The raw materials for preparing the first active substance are: the first active substance (primary graphite particles, Shanshan Technology P15), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the first active substance, the binder, the styrene-butadiene rubber latex, and the conductive agent is 94.5:2:2:1.5. The preparation method of the first active substance: the raw materials are mixed and the viscosity is adjusted to 2200mPa·s by a solvent.

[0055] The raw materials for preparing the second active material are: the second active material (secondary graphite particles, Xingcheng Graphite HRG), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotubes = 1:1; carbon black: Super-p; carbon nanotubes: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the second active material, the binder, the styrene-butadiene rubber latex, and the conductive agent is 95.5:2:2:0.5. The preparation method of the second active material is as follows: the raw materials are mixed and the viscosity is adjusted to 3300mPa·s by a solvent.

[0056] A method for preparing a multilayer electrode comprises the following steps:

[0057] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0058] S2, coating the first active material and the second active material on the conductive layer 2 by double-layer coating, wherein the wet thickness of the first active material is 300 microns, and the wet thickness of the second active material is 600 microns. After drying, the first active material layer 3 and the second active material layer 4 are obtained on the conductive layer 2.

[0059] Example 2

[0060] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0061] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0062] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0063] The raw materials for preparing the conductive paste are: a conductive agent (carbon black, Super-p), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:99.

[0064] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0065] The raw materials for preparing the first active substance are: the first active substance (secondary graphite particles, Xingcheng Graphite HRG), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotubes = 1:1; carbon black: Super-p; carbon nanotubes: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the first active substance, the binder, the styrene-butadiene rubber latex, and the conductive agent is 94.5:2:2:1.5. The preparation method of the first active substance is: the raw materials are mixed and the viscosity is adjusted to 2200mPa·s by a solvent.

[0066] The raw materials for preparing the second active material are: the second active material (silicon carbon), a binder (sodium carboxymethyl cellulose), a styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the second active material, the binder, the styrene-butadiene rubber latex, and the conductive agent is 95.5:2:2:0.5. The preparation method of the second active material is: the raw materials are mixed and the viscosity is adjusted to 3300mPa·s by a solvent.

[0067] A method for preparing a multilayer electrode comprises the following steps:

[0068] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0069] S2, coating the first active material and the second active material on the conductive layer 2 by double-layer coating, wherein the wet thickness of the first active material is 250 microns, and the wet thickness of the second active material is 500 microns. After drying, the first active material layer 3 and the second active material layer 4 are obtained on the conductive layer 2.

[0070] Example 3

[0071] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0072] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0073] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0074] The raw materials for preparing the conductive paste are: a conductive agent (carbon black, Super-p), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:99.

[0075] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0076] The raw materials for preparing the first active substance are: the first active substance (secondary graphite particles, Xingcheng Graphite HRG), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotubes = 1:1; carbon black: Super-p; carbon nanotubes: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the first active substance, the binder, the styrene-butadiene rubber latex, and the conductive agent is 94.5:2:2:1.5. The preparation method of the first active substance is: the raw materials are mixed and the viscosity is adjusted to 2200mPa·s by a solvent.

[0077] The raw materials for preparing the second active material are: the second active material (primary graphite particles, Shanshan Technology P15), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the second active material, the binder, the styrene-butadiene rubber latex, and the conductive agent is 95.5:2:2:0.5. The preparation method of the second active material is: the raw materials are mixed and the viscosity is adjusted to 3300mPa·s by a solvent.

[0078] A method for preparing a multilayer electrode comprises the following steps:

[0079] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0080] S2, coating the first active material and the second active material on the conductive layer 2 by double-layer coating, wherein the wet thickness of the first active material is 300 microns, and the wet thickness of the second active material is 600 microns. After drying, the first active material layer 3 and the second active material layer 4 are obtained on the conductive layer 2.

[0081] Example 4

[0082] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0083] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0084] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0085] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0086] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0087] The raw materials for preparing the first active substance are: the first active substance (hard carbon, Shenzhen Bettery BHC), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the first active substance, the binder, the styrene-butadiene rubber latex, and the conductive agent is 94:2:2.5:1.5. The preparation method of the first active substance is: the raw materials are mixed and the viscosity is adjusted to 2200mPa·s by a solvent.

[0088] The raw materials for preparing the second active material are: the second active material (primary graphite particles, Shanshan Technology P15), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the second active material, the binder, the styrene-butadiene rubber latex, and the conductive agent is 95.5:2:2:0.5. The preparation method of the second active material is: the raw materials are mixed and the viscosity is adjusted to 3300mPa·s by a solvent.

[0089] A method for preparing a multilayer electrode comprises the following steps:

[0090] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0091] S2, coat the first active material on the conductive layer 2 by a single-layer coating method, with a wet thickness of 200 microns, dry, then coat a layer of conductive slurry on the surface of the coating coated with the first active material, with a wet thickness of 30 microns, dry, then coat the second active material on the above-mentioned electrode by a single-layer coating method, with a coating thickness of 500 microns, and dry.

[0092] Example 5

[0093] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0094] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0095] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0096] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0097] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0098] The raw materials for preparing the first active substance are: the first active substance (activated carbon, Japan Kuraray YP-50), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the first active substance, the binder, the styrene-butadiene rubber latex, and the conductive agent is 91:3:2.5:3.5. The preparation method of the first active substance is: the raw materials are mixed and the viscosity is adjusted to 1250 mPa·s by a solvent.

[0099] The raw materials for preparing the second active material are: the second active material (secondary graphite particles, Xingcheng Graphite HRG), a binder (sodium carboxymethyl cellulose), a styrene-butadiene rubber latex (Japan Aiyulong SBR latex, AL-3001A), a conductive agent (mass ratio, carbon black: carbon nanotubes = 1:1; carbon black: Super-p; carbon nanotubes: Tiannai, LB100), and a solvent (deionized water). The weight ratio of the second active material, the binder, the styrene-butadiene rubber latex, and the conductive agent is 95.5:2:2:0.5. The preparation method of the second active material is as follows: the raw materials are mixed and the viscosity is adjusted to 3000mPa·s by a solvent.

[0100] A method for preparing a multilayer electrode comprises the following steps:

[0101] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0102] S2, coating the first active material and the second active material on the conductive layer 2 by double-layer coating, wherein the wet thickness of the first active material is 150 microns, and the wet thickness of the second active material is 650 microns. After drying, the first active material layer 3 and the second active material layer 4 are obtained on the conductive layer 2.

[0103] Example 6

[0104] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0105] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0106] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0107] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0108] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0109] The raw materials for preparing the first active material are: the first active material (single crystal ternary material, Qingdao Xinzheng N5), binder (PVDF glue, DuPont DISP30), conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), solvent (N-methylpyrrolidone). The weight ratio of the first active material, binder, and conductive agent is 93:2.5:4.5. The preparation method of the first active material: mix the raw materials and adjust the viscosity to 8000mPa·s by solvent.

[0110] The raw materials for preparing the second active material are: the second active material (polycrystalline ternary material, Beijing Dangsheng ME5E5), binder (PVDF glue, DuPont DISP30), conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), solvent (N-methylpyrrolidone). The weight ratio of the second active material, binder, and conductive agent is 95:2.5:2.5. The preparation method of the second active material: mix the raw materials and adjust the viscosity to 12000mPa·s by solvent.

[0111] A method for preparing a multilayer electrode comprises the following steps:

[0112] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0113] S2, coating the first active material and the second active material on the conductive layer 2 by double-layer coating, wherein the wet thickness of the first active material is 150 microns, and the wet thickness of the second active material is 250 microns. After drying, the first active material layer 3 and the second active material layer 4 are obtained on the conductive layer 2.

[0114] Example 7

[0115] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0116] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0117] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0118] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0119] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0120] The raw materials for preparing the first active material are: the first active material (single crystal ternary material, Qingdao Xinzheng N5), binder (PVDF glue, DuPont DISP30), conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), solvent (N-methylpyrrolidone). The weight ratio of the first active material, binder, and conductive agent is 93:2.5:4.5. The preparation method of the first active material: mix the raw materials and adjust the viscosity to 12000mPa·s by solvent.

[0121] The raw materials for preparing the second active material are: the second active material (polycrystalline ternary material, Beijing Dangsheng ME5E5), binder (PVDF glue, DuPont DISP30), conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), solvent (N-methylpyrrolidone). The weight ratio of the second active material, binder, and conductive agent is 95:2.5:2.5. The preparation method of the second active material: mix the raw materials and adjust the viscosity to 16000mPa·s by solvent.

[0122] A method for preparing a multilayer electrode comprises the following steps:

[0123] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0124] S2, coating the first active material and the second active material on the conductive layer 2 by double-layer coating, wherein the wet thickness of the first active material is 150 microns, and the wet thickness of the second active material is 250 microns. After drying, the first active material layer 3 and the second active material layer 4 are obtained on the conductive layer 2.

[0125] Example 8

[0126] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0127] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0128] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0129] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0130] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0131] The raw materials for preparing the first active substance are: the first active substance (NCM ternary material, Beijing Dangsheng ME5E5; the mass ratio of the mixture of ME5E5 and activated carbon is 2:3), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the first active substance, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active substance is: mixing the raw materials, pressing the sheets, and obtaining a film sheet with a film thickness of 150 microns.

[0132] The raw materials for preparing the second active material are: the second active material (activated carbon), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the second active material, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active material is: mixing the raw materials, pressing into a sheet, and obtaining a film sheet with a film thickness of 250 microns.

[0133] A method for preparing a multilayer electrode comprises the following steps:

[0134] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0135] S2, laminating the first active material layer 3 and the second active material layer 4 onto the current collector 1 coated with the conductive paste by thermal lamination.

[0136] Example 9

[0137] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0138] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0139] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0140] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0141] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0142] The raw materials for preparing the first active substance are: the first active substance (secondary graphite particles, Xingcheng Graphite HRG), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the first active substance, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active substance is: mixing the raw materials, pressing the sheets, and obtaining a film sheet with a film thickness of 250 microns.

[0143] The raw materials for preparing the second active substance are: the second active substance (hard carbon), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the second active substance, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active substance is: mixing the raw materials, pressing into a sheet, and obtaining a film sheet with a film thickness of 250 microns.

[0144] A method for preparing a multilayer electrode comprises the following steps:

[0145] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0146] S2, laminating the first active material layer 3 and the second active material layer 4 onto the current collector 1 coated with the conductive paste by thermal lamination.

[0147] Example 10

[0148] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0149] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0150] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0151] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0152] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0153] The raw materials for preparing the first active substance are: the first active substance (silicon carbon, Shanshan Technology AS6), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the first active substance, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active substance is: mixing the raw materials, pressing the sheets, and obtaining a film sheet with a film thickness of 150 microns.

[0154] The raw materials for preparing the second active substance are: the second active substance (hard carbon), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the second active substance, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active substance is: mixing the raw materials, pressing the sheets, and obtaining a film sheet with a film thickness of 200 microns.

[0155] A method for preparing a multilayer electrode comprises the following steps:

[0156] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0157] S2, laminating the first active material layer 3 and the second active material layer 4 onto the current collector 1 coated with the conductive paste by thermal lamination.

[0158] Embodiment 11

[0159] A multilayer electrode, such as Figure 1 As shown, from bottom to top, they are: current collector layer 1 , conductive layer 2 , first active material layer 3 and second active material layer 4 .

[0160] The current collector layer 1 is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with 2.5wt% oxalic acid solution for 3.5h.

[0161] The conductive layer 2 is prepared from a conductive paste, the first active material layer 3 is prepared from a first active material, and the second active material layer 4 is prepared from a second active material.

[0162] The raw materials for preparing the conductive paste are: a conductive agent (mass ratio, carbon black: carbon nanotube = 1:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), a binder (sodium carboxymethyl cellulose), styrene-butadiene rubber and deionized water. The mass ratio of the conductive agent, the binder and the styrene-butadiene rubber is 10:0.8:0.5, and the weight ratio of the conductive agent to the deionized water is 1:98.

[0163] The preparation method of the conductive slurry is as follows: conductive carbon black Super-p (Switzerland) is diluted in deionized water and dispersed evenly; a 3.5wt% sodium carboxymethyl cellulose solution that has been uniformly dissolved in advance is slowly and evenly added to the above liquid, mixed evenly, and then a 50wt% concentration of styrene-butadiene rubber solution is poured into the above liquid, mixed evenly to prepare the conductive slurry.

[0164] The raw materials for preparing the first active substance are: the first active substance (hard carbon), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the first active substance, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active substance is: mixing the raw materials, pressing into a sheet, and obtaining a film sheet with a film thickness of 250 microns.

[0165] The raw materials for preparing the second active material are: the second active material (activated carbon), a binder (5wt%, PVDF glue, DuPont DISP30), a conductive agent (mass ratio, carbon black: carbon nanotube = 9:1; carbon black: Super-p; carbon nanotube: Tiannai, LB100), and a lubricant. The weight ratio of the second active material, the binder, the conductive agent, and the lubricant is 85:5:4.5:0.5. The preparation method of the first active material is: mixing the raw materials, pressing into a sheet, and obtaining a film sheet with a film thickness of 250 microns.

[0166] A method for preparing a multilayer electrode comprises the following steps:

[0167] S1, coating the conductive slurry on the current collector layer 1, and after drying, preparing the current collector layer 1 coated with the conductive layer 2;

[0168] S2, laminating the first active material layer 3 and the second active material layer 4 onto the current collector 1 coated with the conductive paste by thermal lamination.

[0169] Performance Testing Methods

[0170] In the above embodiments, embodiments 1, 2, 3, 4, 5, 9, 10, and 11 are used as negative electrodes, and embodiments 7, 8, and 9 are used as positive electrodes.

[0171] The positive and negative electrodes are made into a battery cell in a laminated battery cell structure, and the number of positive and negative electrodes is 9 positive electrodes and 10 negative electrodes. The positive electrode of the negative electrode embodiment adopts the positive electrode prepared in Example 7 of the embodiment; the negative electrode of the positive electrode embodiment adopts the negative electrode prepared in Example 9 of the embodiment. The electrode liquid adopts the formula EC:EMC=1:1, 1.2mol / L LiPF6, 0.5%VC.

[0172] After the battery cells were prepared, they were subjected to a 5C rate discharge test. The results are shown in Table 1.

[0173] Performance test data

[0174] Table 1

[0175]

[0176]

Claims

1. A multilayer electrode, characterized in that: The invention comprises, from bottom to top, a current collector layer (1), a conductive layer (2), a first active material layer (3) and a second active material layer (4).

2. The multilayer electrode according to claim 1, characterized in that The conductive paste of the conductive layer (2) is prepared from raw materials including: a conductive agent and a binder, wherein the mass ratio of the conductive agent to the binder is (5-20): (0.4-4), the conductive agent includes carbon nanotubes, and the aspect ratio of the carbon nanotubes is greater than 500.

3. The multilayer electrode according to claim 2, characterized in that The first active material layer (3) has a proportion of the first active material greater than 80 wt %, and the second active material layer (4) has a proportion of the second active material greater than 80 wt %.

4. The multilayer electrode according to claim 3, characterized in that The first active material includes at least one of the following negative electrode active materials or positive electrode active materials; the negative electrode active material includes: primary particle graphite, secondary particle graphite, silicon carbon, hard carbon; the positive electrode active material includes: activated carbon, single crystal ternary material, polycrystalline ternary material, lithium manganese oxide material, lithium iron phosphate material, layered oxides that can be used for sodium ion batteries, Prussian blue compounds, Prussian white compounds, and polyanionic compounds.

5. The multilayer electrode according to claim 4, characterized in that The second active material includes at least one of the following negative electrode active materials or positive electrode active materials; the negative electrode active material includes: primary particle graphite, secondary particle graphite, silicon carbon, hard carbon; the positive electrode active material includes: activated carbon, single crystal ternary material, polycrystalline ternary material, lithium manganate material, lithium iron phosphate material, layered oxides that can be used for sodium ion batteries, Prussian blue compounds, Prussian white compounds, polyanionic compounds; the D50 particle size of the primary particle graphite is 10-30 microns, and the D50 particle size of the secondary particle graphite is 5-15 microns.

6. A method for preparing a multilayer electrode according to any one of claims 1 to 5, characterized in that: The method comprises one of the following methods: wet coating and dry multi-layer lamination.

7. The method for preparing a multilayer electrode according to claim 6, characterized in that: The wet coating process comprises the following steps: S1, coating a conductive slurry on a current collector layer (1), and after drying, preparing a current collector layer (1) coated with a conductive layer (2); S2, applying the first active material slurry and the second active material slurry onto the conductive layer (2), and after drying, obtaining the first active material layer (3) and the second active material layer (4) on the conductive layer (2).

8. The method for preparing a multilayer electrode according to claim 7, characterized in that: The dry multi-layer lamination comprises the following steps: firstly making a single-layer dry electrode membrane, then laminating a plurality of single-layer dry electrode membranes in a multi-layer manner, and finally laminating the laminated electrode membrane with a current collector layer (1).

9. The method for preparing a multilayer electrode according to claim 8, characterized in that: The viscosity of the first active substance in the first active substance layer (3) at 25°C is 1800-12000 mPa·s; the thickness of the first active substance layer (3) is 120-350 microns; the viscosity of the second active substance in the second active substance layer (4) at 25°C is lower than the viscosity of the first active substance, and the difference between the two viscosities is not less than 1000 mPa·s; the thickness ratio of the first active substance layer (3) to the second active substance layer (4) is (1-2):(1-4).

10. The method for preparing a multilayer electrode according to claim 9, characterized in that: The current collector layer (1) is a copper foil after corrosion treatment, and the corrosion conditions are: corrosion with a 2.5 wt% acid solution for 2 h to 5 h.